2000
DOI: 10.1046/j.1365-2036.2000.014s1044.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of NSAIDs and a COX‐2 specific inhibitor on Helicobacter pylori‐induced PGE2 and HGF in human gastric fibroblasts

Abstract: Summary Background: There is compelling evidence for the pivotal role of Helicobacter pylori in the pathogenesis of gastrointestinal ulcer disease. However, despite the bacterium's toxicity, the majority of H. pylori infections are not accompanied by gastric ulcers. This implies the existence of a host mechanism offsetting H. pylori toxicity. Aims: To evaluate gastric fibroblasts' expression of hepatocyte growth factor (HGF), which is known to facilitate gastric ulcer healing, in the presence of H. pylori; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Until now, the anti-cancer mechanism of aspirin remains unclear. It is possible that aspirin may inhibit the replication and proliferation of H. pylori, and neutralize the increased COX-2 expression and prostaglandin synthesis associated with H. pylori infection, thereby reducing the risk of gastric cancer [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the anti-cancer mechanism of aspirin remains unclear. It is possible that aspirin may inhibit the replication and proliferation of H. pylori, and neutralize the increased COX-2 expression and prostaglandin synthesis associated with H. pylori infection, thereby reducing the risk of gastric cancer [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…3) Gridley et al [47] and Thun et al [48] indicated that nonsteroidal anti-inflammatory drugs (NSAIDs) may protect patients against gastric cancer as well as colorectal cancer. Wang et al [49] reported that NSAID use has been associated with a reduced risk of gastric cancer and speculated that it is possible that NSAIDs may inhibit the replication and proliferation of H. pylori [49,50], while Takahashi et al [51] and Hudson et al [52] reported that NSAIDs may neutralize the increased cyclooxygenase-2 (COX-2) expression and prostaglandin synthesis associated with H. pylori infection, thereby reducing the risk of gastric cancer. However, these drugs may also cause peptic ulcers [53], so that long-term NSAID use may be associated with an increased risk of gastroduodenal ulcer and a reduced risk of gastric cancer, but there are some negative opinions about this association [54,55], and so there is no consensus regarding the anticancer effects of NSAIDs.…”
Section: Frequencies Of Duodenal Ulcer and Gastric Cancermentioning
confidence: 99%
“…Takahashi et al . reported that H. pylori increased the PGE 2 and HGF releases from human gastric fibroblasts and that these increased releases were inhibited by NSAIDs including a COX‐2 specific inhibitor 50 . Several studies showed that H. pylori infection can cause increased gastric cell proliferation, which is assumed to play an important role in gastric carcinogenesis 6 –8 .…”
Section: Discussionmentioning
confidence: 99%